An Analysis of the Inner Conflict of Seokjin’s Character in Seok-Jun Yoon’s the Most Beautiful Moment in Life Novel - Valen Kingkin Adishapsa; Widyashanti Kunthara Anindita (Applied Research on English Education (AREE), 2023)
Abdurrahman. (2003). Evaluasi pembelajaran bahasa dan sastra Indonesia. FBS UNP.The purpose of this study is to find out the structure that builds the novel and the inner conflicts experienced by Seokjin, this can be seen from the inner conflict that occurs in Seokjin’s character in The Most Beautiful Moment in Life Novel by Seok-jun Yoon: Literary Psychology Approach according to Kurt Lewin’s theory. The research method used is a descriptive method using qualitative analysis, namely describing the inner conflict that occur in Seokjin. Data collection is taken by reading and taking notes. The source of this research is The Most Beautiful Moment in Life Novel by Seok-jun Yoon with a total of 229 pages published by beORIGIN, 2019. The research result of the structure that build The Most Beautiful Moment in Life Novel found 2 data of theme, 6 data of plot, 16 data of setting, and 14 data of characterization. The analysis of inner conflict in The Most Beautiful Moment in Life Novel show that there are 3 types of inner conflict found in the novel, namely, approach – approach conflict, approach – avoidance conflict, and avoidance – avoidance conflict. There are 2 data found in approach – approach conflict, 9 data found in approach – avoidance conflict, and 5 data found in avoidance – avoidance conflict.